PENINGKATAN KEMAMPUAN MENGENAL HURUF DAN ANGKA KELAS A MENGGUNAKAN MEDIA GAMBAR PADA KELOMPOK BERMAIN (KB) TUNAS BANGSA KECAMATAN SEJANGKUNG TAHUN AJARAN 2022-2023 - Nurul Atika; Saripah; Zuri Astari (Samawa (Sakinah, Mawaddah Warahmah), 2024)
The aim of this research is to explain: 1) How to plan to improve the recognition of letters and numbers in Class A using image media in the Tunas Bangsa Play Group (KB). 2) How to implement the application of image media in improving the ability to recognize letters and numbers in Class A using image media in the Tunas Bangsa Play Group (KB). 3) How to evaluate the use of image media in improving the ability to recognize letters and numbers in Class A Using Image Media in the Tunas Bangsa Play Group (KB). This research uses a qualitative approach. The type of research carried out is phenomenological research. Data collection techniques use observation, interviews and documentation. The research results show that: (1) Planning to improve recognition of Class A letters and numbers using image media in the Tunas Bangsa Play Group (KB). Namely by making a RPPH (Learning Implementation Plan) which is structured and directed in accordance with the applicable curriculum. (2) Implementation of the application of image media to improve the ability to recognize letters and numbers in Class A using image media in the Tunas Bangsa Play Group (KB). Namely by using image media in the form of posters. (3) Evaluation of the use of image media in improving the ability to recognize letters and numbers in Class A Using Image Media in the Tunas Bangsa Play Group (KB). Namely by implementing an oral test. The evaluation results obtained were an increase in children's ability to recognize letters and numbers. Because with increasing ability to recognize letters and numbers students will be able to read and write.